Skrining Fitokimia Minuman Tradisional Moke dan Sopi sebagai Kandidat Antimikroba - Annytha Ina Rohi Detha; Frans Umbu Datta (JURNAL KAJIAN VETERINER, 2019)
Sopi and moke of East Nusa Tenggara Province are some traditional beverage made from nira or interest leads palm (Borassus flabellifer L.). Several studies have shown that sopi and moke have an antimicrobial activity. Antimicrobial activity of plants derivatives may be influenced by the content of phytochemical compounds. The purpose of this study was to determine the class of phytochemical compounds in sopi and moke. Phytochemical testing performed on seven chemical compounds, namely alkaloids, flavonoids, phenols hydroquinone, steroids, triterphenoid, tannins and saponins. The results show that sopi contains of alkaloids and moke contains of phenol hydroquinone and saponins. Antimicrobial activity of sopi and moke supposed to be caused by these three compounds and this could be a potential source of an alternative disinfectant candidate.